CONSERVATION AND MANAGEMENT PLAN AT A PREHISTORIC ARCHAEOLOGICAL SITE : THE CASE OF THE NIAH CAVES IN SARAWAK, MALAYSIA - Nur Auni, Ugong; Nicholas, Gani; DG. JUNAIDAH, AWANG JAMBOL; NURULASYIKIN, HASSAN; ABDUL RAHMAN, MAD ALI ABANG (UMT Press, 2024)
The Niah Caves are an important archaeological site that supports a resident population and is host to a large and growing number of visitors. Close monitoring, strict regulations and careful management will be required in the long term to avoid pressures and threats from urban expansion, plantations, resource use, village growth, excessive tourist infrastructure and use, and service development. However, the absence of a formally written conservation and management plan prior to 2022 has left the heritage conservation and management of the Niah Cave site insufficient in addressing its management challenges. Hence, this paper analyses the conservation and management plan for the site through systematic observation, site analysis, and stakeholder interviews. The research focuses on documentation and recording, assessing the site’s importance, identifying all factors and issues, defining management policy, selecting management strategies, and monitoring and reviewing the plans for the site. The study aims to contribute to the conservation and preservation of the Niah Caves as a national park in Sarawak. Emphasis is placed on prioritising the preservation and management of archaeological sites and advocating for comprehensive planning and sustainable management practices for the conservation of cultural heritage.